Risk propagation in emergency supply chain during public health events - From a reliability perspective - Weiting Sun; Wenzhu Liao (Heliyon)
The emergency supply chain is a vital component of the emergency management system and serves as the cornerstone for delivering relief during emergencies. This paper focuses on investigating the propagation mechanism of supply chain risks in public health emergencies. Firstly, by analyzing the characteristics of emergency supply chains, this study enhances the formation mechanism of scale-free networks in emergency supply chains from a reliability perspective through the utilization of Decision Experimentation and Evaluation Laboratory (DEMATEL) and Analytic Network Process (ANP) methods. Secondly, an emergency supply chain network is established based on the improved mechanism. Thirdly, the risk propagation mechanism of the emergency supply chain is analyzed by utilizing an enhanced outbreak model. The mechanisms and processes of risk propagation in the emergency supply chain are examined in relation to the initial proportion of infection, intensity of risk, probability of infection, probability of recovery and speed of rescue. Based on this analysis, factors influencing risk propagation are identified and effective measures for controlling risks are proposed.